2023
DOI: 10.1038/s41598-023-43432-z
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study on the mechanical response of thermal-pressure rejuvenated CuxZr100−x metallic glasses

S. Sayad,
M. Khanzadeh,
Gh. Alahyarizadeh
et al.

Abstract: A molecular dynamics study was performed on the mechanical response of thermal-pressure rejuvenated CuxZr100−x metallic glasses. The effect of temperature (50, 300, 600 K) and pressure (0–50 GPa) on the rejuvenation process and the mechanical properties of CuxZr100−x including stress–strain response, shear localization formation and elastic modulus were investigated. The thermal-pressure rejuvenation process involves transitioning the system to a higher potential energy state and a lower atomic volume, demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…We have extended our examination to encompass additional mechanical properties that can be derived from the elastic constants, the elastic constants, as described in refs 45 , 46 , and elucidated in the methods section. Comprehensive mechanical behavior regarding these derived properties can be found in the supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
“…We have extended our examination to encompass additional mechanical properties that can be derived from the elastic constants, the elastic constants, as described in refs 45 , 46 , and elucidated in the methods section. Comprehensive mechanical behavior regarding these derived properties can be found in the supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
“…Structure analysis of both experiments and simulations has revealed that the SRO of metallic glasses is often described by the presence of icosahedral structures, i.e., a center atom enclosed by 12 atoms, which control many physical properties in these systems [50,51]. Although the atomic structure can be defined through the VA based on the following criteria: the lines that connect the central atom and its nearest neighbors are bisected using a set of planes, constructing thus a polyhedron [38,52]. Each polyhedron i is recognized using the Voronoi index < > n n n n , , ,…”
Section: Resultsmentioning
confidence: 99%
“…6 in which ( ) = n j 3,4,5,6 i j presents the number of j-edged polygon in Voronoi Polyhedron (VP) i [38,52]. Figure 4 shows the response of the structural atomic packing at SRO in Ta MG to the external pressure ranging from 0 GPa to 70 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Their high strength combined with the good plasticity, supercooled liquid region, and high glass transition temperature makes them attractive materials for functional and practical applications. [4,5] In the same context, Cu-Zr-based MGs have attracted much more attention scientifically and commercially due to their higher glass-forming ability (GFA), their mechanical properties as well as their low cost in the range of materials. [6,7] Improved ductility under compression and exceptional plasticity are also reported for Cu-Zr-based MGs.…”
Section: Introductionmentioning
confidence: 99%